P204 Fractionated Carboplatin and Vinorebine For Elderly and Poor Performance Status Patients with NSCLC. (19th November 2012) - Maguire, J; Datta, S; Kelly, V; Mbanu, P
Abstract : Patients with advanced NSCLC who are elderly and/or have poor Performance Status are generally considered unsuitable for chemotherapy and usually excluded from the possible benefits of systemic treatment. The outlook for this group of patients is poor, with typical survival times of four months or less. If a tolerable form of systemic chemotherapy could be identified for elderly and poor PS patients, this would enable consideration of active rather than supportive care, and might improve overall survival rates. We have treated 110 patients who were either aged over 70; (16%, n=18), PS 2 or greater (36%, n=40) or both; (46%, n=52) with systemic chemotherapy using fractionated Carboplatin and Vinorelbine. Carboplatin was administered at AUC 2.5 on day 1 and day 8, with oral Vinorelbine 60 mg/m2 on a 21 day cycle. 40 patients had Stage III and 68 had Stage IV disease. Prophylactic levofloxacin 500 mg daily was given from day 9 to 20 of each treatment cycle. Renal function for Carboplatin dosage was measured using EDTA clearance. 67 patients were aged 70 or greater, and 22 more than 80 years. 90 patients were PS 2 or 3 and 51 patients were both over 70 and had poor PS. The average number of cycles given to each patient was 3. 7% of patients died within 30 days of receiving chemotherapy treatment. The median survival for the whole patient group was 7.5 months. 72% percent of patients lived for 6 months or longer from commencement of chemotherapy. 40% of patients lived 9 months or longer and 22% of patients lived for a year or longer after starting chemotherapy. There was a strong statistical correlation between response to chemotherapy and survival. In conclusion, systemic chemotherapy using fractionated Carboplatin and Vinorelbine should be considered as a possible treatment option for patients with advanced NSCLC who are elderly or have moderate to poor PS.